Improving food security in developing countries: a role for the IMF - KIRKPATRICK, C.H. (PSL Quarterly Review, 2013)
The focus of the present paper is upon the problem of short-term food insecurity, as manifested in variability in year to year per capita consumption. The author argues that fluctuations in per capita food consumption levels are the direct result of a shortage of foreign exchange which limits the capacity of low income countries to obtain the level of food imports necessary to offset a sudden shortfall in domestic production and/or an increase in world prices. It is suggested, therefore, that the international community could play a significant role in the alleviation of the food insecurity problem in LDCs through the provision concessionary finance for the funding of exceptional food import requirements. JEL: F31, F33, Q18